DESIGN & DEVELOPMENT WITH WEB OF MANAGEMENT SYSTEM INFORMATION DEWAN KEMAKMURAN MASJID JAMI AL – MUHAJIRIN, TANGERANG - Nurdiana Handayani; Hendra Mayatopani; Rachmat Destriana (University of Muhammadiyah Tangerang, 2021)
Jami' Al - Muhajirin Mosque is one of the large mosques located in the Tangerang Elok Villa housing estate, Kutajaya Village, Pasar Kemis District. Activities carried out in this mosque are not only religious activities but also social activities. In managing the secretariat administration and finances, mosque administrators still experience difficulties such as the process of recording, searching and making reports that are still semi-computerized, while the process is considered less effective and efficient.And for the congregation of the mosque if they want to need information about the mosque, they must come to the mosque and see directly the information board in the mosque. There needs to be innovation by applying technology in the mosque management system internally to make it easier to manage mosque management. The type of research used in this study is a case study (Case Study Research) with a qualitative method while in developing and making this application using the waterfall method. The blue print of the system design is visualized using the Unified Modeling Language with use case diagrams and system testing is carried out by the admin and chairman of the Mosque's DKM on the functional system. This web-based management information system provides convenience for administrators in managing mosque and congregation management data in finding information related to Al-Muhajirin mosque data.Keywords: Information Systems, Mosque Prosperity Council Management, Waterfall, Web